Performance management : happiness and keeping pace with technology - Arora, Madhu (Economist); Khurana, Poonam; Choiden, Sonam (Boca Raton, FL : CRC Press, Taylor & Francis Group, 2021)
"The book covers various domains of performance management in management and information technology and will include topics related to the performance of digital wallets from the customer point of view, evaluating sustainability of microfinance institutions, challenges in employee retention, problems faced by the work force in information technology and management, dimensions of happiness for women in the workplace, the role of happiness in building a meaningful life, and quality of work life"--
OCLC-licensed vendor bibliographic record.
Keywords: Performance -- Management; Employees -- Rating of; Personnel management -- Technological innovations; TECHNOLOGY / Manufacturing